Obesity prevention advocacy in Australia: an analysis of policy impact on autonomy - Emily Haynes; Roger Hughes; Dianne P. Reidlinger (Elsevier, 2017)
Abstract Objective: To explore obesity policy options recommended by stakeholders and identify their impact on individual autotomy. Methods: Qualitative and quantitative methods were used. A content analysis of submissions to the Australian Government's Inquiry into Obesity was conducted. Each recommendation was categorised by its impact on autonomy, according to existing frameworks. Chi‐square test for independence was used to explore the association between autonomy and stakeholder support defined as frequency of recommendation. Results: The extent of support for a policy option was significantly associated with impact on autonomy (p<0.001). Options that reduce autonomy were least frequently recommended in every setting; but more likely in schools (27%) than other settings (<1%). Recommendations to provide incentives (9%) were more common than disincentives (2%) or restrictions (3%), and those that enhance autonomy were most widely recommended (46%). Conclusions: Stakeholders advocated policy options that enhance individual autonomy to a greater extent than those that diminish autonomy. Implications for public health: Targeting obesity policy options that enhance rather than diminish autonomy may be more politically acceptable across most settings, with the exception of schools where more restrictive policy options are appropriate. Re‐framing options accordingly may improve leadership by government in obesity policy.